TINGKAT KESUKAAN KONSUMEN TERHADAP IKAN BUDI DAYA AIR TAWAR - Desmelati ' (Fakultas Perikanan dan Kelautan, Universitas Riau, 2010)
This study was carried to observe some of factors influencing theselection of aquacultured freshwater fishes (patin and tilapia) by consumers.Among factors observed were the knowledge, attitude and behavior ofrespondents toward the aquacultured fishes. Two hundred and fifty respondentsaged between 15-55 old were interviewed. They were randomly selected fromareas such as at popular shopping complexes, bus stations and UniversityKebangsaan Malaysia campus around Kajang and Bandar Baru Bangi. Range ofscore for “knowledge” was 0-25, attitude 0-75 and behaviour 0-40. Resultsshowed that the average score for knowledge was11.5±3.4, attitude 58.5±4.3 andbehavior 23.5±3.4 of respondent the intake of aquacultured freshwater fish.Pearson correlation’s showed relation between knowledge and level of education(r = 0.76) and behavior (r = 0.85) of respondent toward the selection and intake ofaquacultured freshwater fish in their diet.